ECOS CONSTITUCIONALES EN SISTEMAS REGIONALES - López Chaverri, José Francisco (2021)
In the case of the impressive amount of legal literature that has emerged as a result of the unfolding European project in its different stages (founding of the ECSC, the European Economic Community, etc.) the allusion to the existence of a constitutionalizing process is clear and reiterated. Such a link has even been alluded to accentuate the difference between the European scheme and other analogous structures in transnational contexts; situation which motivates to deepen an exploration of the proposed relationship. In the specific case of legal analyzes of the European phenomenon -as an archetype for other movements with a regional character within a globalized context-, many studies tend to address particularities of the respective systems, but without raising further reflections over the legal-political approaches that may arise due to the assumptions or the extension of such regional arrangements. Considering the above, the following study aims to examine certain ideas that could facilitate a generalizable legal approach over such issues and allow a analysis of organizations under such kind of regional institutionality.